2002
DOI: 10.1016/s1567-5769(01)00173-4
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis

Abstract: Allergic contact dermatitis (ACD) is a common occupational and environmental health issue. In common with other forms of allergy the disease progresses in two stages; an initial phase during which sensitization is acquired, followed later (after subsequent exposure to the same chemical allergen) by elicitation of a cutaneous inflammatory reaction. The development of skin sensitization is associated with, and requires, the activation and clonal expansion of allergen responsive T lymphocytes and it is these cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
153
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(157 citation statements)
references
References 54 publications
0
153
0
4
Order By: Relevance
“…CA has not previously been investigated with respect to autoimmune diseases, probably because CA has not been regarded as a Th2-dominated illness [24]. However, recent studies have found that in patients with long-lasting dermatitis, as in the present patient material, a Th2 response is anticipated [25,26].…”
Section: Discussionmentioning
confidence: 93%
“…CA has not previously been investigated with respect to autoimmune diseases, probably because CA has not been regarded as a Th2-dominated illness [24]. However, recent studies have found that in patients with long-lasting dermatitis, as in the present patient material, a Th2 response is anticipated [25,26].…”
Section: Discussionmentioning
confidence: 93%
“…Contact dermatitis is one of the most common skin diseases (11). Knowledge of the pathophysiology of contact dermatitis is derived chiefly from animal models in which the inflammation induced by hapten painting of the skin is referred to as contact hypersensitivity (CHS) (12).…”
Section: T-bet Is Known As a Th1 Lineage Commitment Transcription Facmentioning
confidence: 99%
“…Contact dermatitis and CHS are delayed-type hypersensitivity reactions that are mediated by haptenspecific T cells (12). Skin sensitization resulting in contact dermatitis and CHS is dependent on the initiation of specific T lymphocyte responses (11,13). Until recently it was believed that the most important cells in these responses were CD4 ϩ T lymphocytes.…”
Section: T-bet Is Known As a Th1 Lineage Commitment Transcription Facmentioning
confidence: 99%
“…In order for a chemical to induce skin sensitization, it must satisfy certain requirements (Kimber et al, 2002). First, the chemical must pass through the stratum corneum and gain access to the viable epidermis.…”
Section: Review Articlementioning
confidence: 99%